Encapsulating peritoneal sclerosis in recipient of kidney transplantation – Case report - Takenaka, Vanessa Suemi; Borges, Felipe Sbrolini; Andrade, Thales Franco de; Capelozza, André Petraroia; Braga, Sibele; Schnorr, Gabriel Castilho; Nicolellis, Laís Pacca; Mancero, Jorge Marcelo Padilla; Noronha, Irene L.; David, André Ibrahim (Brazilian Journal of Transplantation, 2016)
Encapsulating Peritoneal Sclerosis (EPS) is a rare and severe condition often associated to Peritoneal Dialysis (PD). It is presented as a mass of fibrous tissue covering visceral tissues that may compromise the physiological function of the whole digestive tract. This study reports a case of EPS caused by a complication of PD due to focal segmental glomerulosclerosis. In the case reported, the patient was submitted to PD and underwent two renal transplantes from living donor. Different surgical techniques were assessed, which have proved useful for clinical improvement of the patient. Parenteral nutrition has significantly contributed to the maintenance of nutrition, assisting in healing and in serum protein, vitamins and electrolytes. Tamoxifen therapy and administration of sodium hyposulfite were effective in retarding the progression of EPS.